Unraveling sources of cyanate in the marine environment: insights from cyanate distributions and production during the photochemical degradation of dissolved organic matter - Wang, Rui; Liu, Jihua; Xu, Yongle; Liu, Li; Mopper, Kenneth (Frontiers in Marine Science, 2024)
Cyanate is a nitrogen and energy source for diverse marine microorganisms, playing important roles in the nitrogen cycle. Despite the extensive research on cyanate utilization, the sources of this nitrogen compound remain largely enigmatic. To unravel the sources of cyanate, distributions and production of cyanate during photochemical degradation of natural dissolved organic matter (DOM) were investigated across various environments, including freshwater, estuarine, coastal areas in Florida, and the continental and slope regions of the North American mid-Atlantic Ocean (NATL). Cyanate production was also examined during the photochemical degradation of exudates from a typical strain of Synechococcus, an important phytoplankton component. To deepen our understanding of the sources and production mechanisms of cyanate, its production was assessed during the photochemical degradation of a natural seawater DOM supplemented with five nitrogen–containing compounds with distinguishing structures and functional groups. Generally, cyanate exhibited higher concentrations in the Florida coastal, estuarine, and freshwater environments than the NATL. However, cyanate distribution did not consistently align with its production rates. Despite significantly low concentrations in the NATL, DOM from this region exhibited cyanate production rates comparable to estuarine and Florida coastal environments. Although relatively high cyanate concentrations were observed in the freshwaters, DOM in this environment exhibited very low cyanate production rates. A highly significant correlation was observed between cyanate and chlorophyll a (Chl a) concentrations in these areas. Moreover, in most estuarine and NATL stations, cyanate concentration and production rate in the Chl a maximum layer were significantly higher than in other layers. Cyanate was produced during the photochemical degradation of the Synechococcus exudates. The cyanate production was significantly enhanced when the natural seawater DOM was supplemented with GlycylGlycine, 4-(methylamino) benzoic acid, 4-[ethyl(methyl)amino] benzaldehyde or methyl 2-aminobenzoate. Our study implies that photochemical degradation of marine DOM, especially phytoplankton-derived DOM, is a substantial source of cyanate in the ocean. Additionally, cyanate may form during the degradation of peptides and small aromatic compounds in DOM, providing novel insights into the nitrogen cycle.